PENYUSUNAN DRAFT STANDARD OPERATING PROCEDURE (SOP) PENGOLAHAN KERIPIK PISANG (STUDI KASUS DI SALAH SATU INDUSTRI RUMAH TANGGA KERIPIK PISANG BANDAR LAMPUNG) - Haryanto, Didit; Nawansih, Otik; Nurainy, Fibra (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
Standard operating procedure (SOP) is a procedure or steps which is standardized and must be passed to complete a particular work process. Arranging SOP draft is based on a review of Good Manufacture Practice. SOP is made for being a guide line in doing process in an industry. Purposes of this research is arranging SOP draft for home industries of banana chips making, so the product will meet the standard. In this research, drafting standard operating procedure (SOP) of the banana chips industry was begun with observating and recording every detail process. The research was conducted through four steps. Firstly, field observation to observateÂ process, including sanitation, tools specification, and description about step of processing banana chips. Second step was determining the critical point and optimating the condition. The next step was arranging the SOP draft. The last was the testing of SOP draft. Then the data were compared and discussed descriptively. Â The result was a SOP draft which was used as in processing banana chips the products consistenly had meet the standard quality of SNI 01-4315-1996, they include moisture content, ash content, fat content, wholeness, with flavor, aroma, color, and texture. Â The analysis data are, Moisture content (0,17%), ash content (1,35%), fat content (27,90%) and wholeness (88,00%). Otherwise the data analysis for banana chips that produce without SOP are, moisture content (0,15%), ash content (1,88%), fat content (39,41%) and wholeness (83,00%). Keywords: standard operating procedure (SOP), banana chips, consistency of quality